AN ASSESSMENT OF THE HUMAN SPIRIT MERLEAUPONTY, LEVI-STRAUSS, FOUCAULT - SIMILARITIES AND DIFFERENCES OF THE HUMAN SCIENCES AND PHILOSOPHY - de Noronha, Nelson Matos (European Scientific Journal, ESJ, 2014)
The theoretical and methodologists progress of the social sciences and also the massive presence of social workers in the social life induces me to describe the facts where philosophy and human sciences crossed each other with the goal to emphasize the problems and the challenges that their relationships puts on the contemporary knowledge’s configuration. To make that, I writhed some remarks about the books of Merleau-Ponty, Lévi-Strauss and Foucault, like Kant’s successors.